Comparative Study between Nasal Endoscopic Findings and Nose and Paranasal Sinus Computerized Tomography in diagnosis of Nose and Paranasal Sinuses Diseases - Al-Assal, Khalid Dahham Radi; Al-Khafaji, Ahmed Abass Mossa; Thuhabat, Jawad AbdulKadhum Beden (AL-Kindy College Medical Journal, 2020)
Background: Nasal obstruction is common in otorhinolaryngology outpatient visitors. The diagnosis of such compliant is by history, clinical examination and diagnostic procedures. Nasal endoscopy and computerized tomography scan are common diagnostic investigations. Nasal obstruction is either anterior or posterior (nasal septal deviations, hypertrophied turbinate pathological cyst, polyps, mass etc), or postnasal obstruction (hypertrophied turbinate, adenoid hypertrophy, nasopharyngeal cyst or nasopharyngeal tumors). Aim of study: Prospective study to compare endoscopic finding and computerized tomography of nose, paranasal sinuses and postnasal space as diagnostic methods for nasal obstruction and other nose, paranasal sinuses and post nasal space diseases. Subjects and methods: 80 patients with nasal obstruction between the age of 12-60 years old.All patient were examined by nasal endoscopy (rigid or flexible) under local anaesthesia (10 % xylocaine spray and cotton wicks soaked with ephidren 0.5 % and xylocaine 2 % ) and nose, paranasal sinuses and post nasal space C.T. scan,weather without contrast or with it, bone window or soft tissue according to the lesion. Results: Both nasal endoscopy and C.T. scan were an important tools for diagnosis of nasal diseases and complementary to each other. Conclusion: Endoscopic examination of the nose gives a real view of nasal structures, postnasal space, any mass or polyps present.Computerized tomography is an accurate diagnostic method of the Nose, paranasal sinuses and post nasal spaces anatomical variations or pathologies.